Pengaruh Struktur Modal, Pertumbuhan Perusahaan, dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Infrastruktur di Indonesia - Tio Waskito Erdi (Jurnal Akuntansi dan Pajak, 2024)
The research was conducted to examine the influence of capital structure, company growth, profitability on company value in infrastructure and transportation sector companies. This type of research is causal-comparative and the data used is secondary data in the form of annual reports and financial reports of infrastructure and transportation companies for the 2020-2023 period. Sample selection was carried out using a purposive sampling method, with a sample of 13 companies. The analysis used is multiple linear regression analysis with the SPSS test tool. The research results showed that together capital structure, company growth and profitability had an effect on company value. Even though the company growth variable has no effect on company value, the variable has a positive directional value.